Implementation of Arabic Learningbased on Multiple Intelligences at Al-Kautsar Elementary School Malang - Rizka Widayanti; Yelfi Dewi (STAI Darul Quran Payakumbuh, 2020)
This paper aims to describe the implementation of Arabic language learning based on multiple intelligences at Al-Kautsar Elementary School Malang which includes initial activities, core activities, and final activities. This research uses descriptive qualitative research methods through case studies with data collection techniques through observation, interviews and documentation. This study shows that the implementation of learning Arabic based on multiple intelligences at SD Al-Kautsar Malang can be developed according to the intelligence clusters of students in the classroom, starting from initial activities, core activities, and final activities. The research findings show that the implementation of Multiple Intelligence-based Arabic learning can provide an overview of the achievement and diversity of activities carried out by teachers and students in the classroom.